2012
DOI: 10.1016/j.hydromet.2011.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The passivation of iron in ammoniacal solutions containing copper (II) ions

Abstract: In the present study it was found that the presence of millimolar amounts of copper (II) ions in ammoniacal solutions leads to the spontaneous formation of a stable passive layer on metallic iron and iron alloys with nickel and cobalt, under conditions in which they would otherwise remain in active dissolution. This finding may be of significance to industrial processes which employ ammoniacal solutions to leach metal values from materials rich in metallic iron, such as, for example, laterite ores which have u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…This is in contrast to the behaviour observed in the presence of copper ions, which under the same conditions were found to promote passivation even at concentrations of an order of magnitude lower (D'Aloya and Nikoloski, 2012 (Figure 1) also being observed on the pitted iron surface. This was thought to consist mainly of iron corrosion products, with the cobalt being present either in its metallic state, due to cementation, or within the iron hydroxides and carbonates, due to adsorption or co-precipitation.…”
Section: The Anodic Dissolution Of Iron In the Presence Of Dissolved contrasting
confidence: 79%
See 2 more Smart Citations
“…This is in contrast to the behaviour observed in the presence of copper ions, which under the same conditions were found to promote passivation even at concentrations of an order of magnitude lower (D'Aloya and Nikoloski, 2012 (Figure 1) also being observed on the pitted iron surface. This was thought to consist mainly of iron corrosion products, with the cobalt being present either in its metallic state, due to cementation, or within the iron hydroxides and carbonates, due to adsorption or co-precipitation.…”
Section: The Anodic Dissolution Of Iron In the Presence Of Dissolved contrasting
confidence: 79%
“…In contrast with the behaviour of iron observed in the presence of copper ammines (D'Aloya and Nikoloski, 2012), where increasing the ammonium bicarbonate concentration at a constant [NH 3 ] T was found to delay passivation, in the presence of cobalt and thiosulfate ions the opposite trend was observed. (Table 3).…”
Section: The Effect Of [Nh 3 ] and [Co 2 ] On Passivation Timementioning
confidence: 65%
See 1 more Smart Citation
“…Malachite experiences a similar case when it reacts with an alkaline ammoniacal solution of ammonium carbonate [25]. Although the conventional alkaline leaching process using cyanide and ammonia can yield recovery percentages close to 90%, its use is limited; even though the ammoniacal leaching medium is intended to selectively extract copper, its use implies technical and environmental risks [16,26,27]. According to these results, it is proposed that the global reaction for the dissolution of basic cupric carbonate (malachite) by the action of tartrate ions in aqueous alkaline medium is represented by the following equation:…”
Section: Evaluation Of the Dissolution Of Basic Cupric Carbonate (Mal...mentioning
confidence: 99%
“…A previous study has found that iron readily passivates in the presence of millimolar amounts of dissolved copper (D'Aloya and Nikoloski, 2012). However studies conducted in ammoniacal-carbonate solutions containing both copper (II) and thiosulfate ions are complicated by the possibility of a homogeneous redox reaction between these two species (Rábai and Epstein, 1992).…”
Section: Introductionmentioning
confidence: 99%